Dermaseptins as potential antirabies compounds. Issue 33 (2nd August 2019) - Mechlia, Mohamed Ben; Belaid, Afifa; Castel, Guillaume; Jallet, Corinne; Mansfield, Karen L.; Fooks, Anthony R.; Hani, Khaled; Tordo, Noël
Abstract: Over the last 20 years, natural peptides playing a key role in defense mechanisms and innate immunity have been isolated from unicellular organisms. Amphibian skin secretes dermaseptins, 24–34 amino acids in length that have a wide antimicrobial spectrum incorporating yeast, fungi, protozoa, bacteria and enveloped viruses. The anti-rabies virus (RABV) activity of dermaseptins S3 (30aa) and S4 (28aa) from Phyllomedusa sauvagei has been investigated, and further dissected its molecular basis by comparing punctual mutation or deletion of S4 analogues. The results showed that: (1) S4 is more active than S3 against RABV infection, 89% versus 38% inhibition at 7.5 μM; (2) the 5 NH2-aa of S4 are crucial for its inhibitory potential (S46 – 28 lost any inhibition) but the COOH terminus stabilizes the inhibitory potential (S41 – 16 showed only 23% inhibition at 7.5 μM); (3) there is a correlation between viral inhibition and dermaseptin cytotoxicity, which remains however moderated for BSR cells (≤12% at 10 μM). A single mutation in position 4 (S4M4K ) slightly reduced cytotoxicity while keeping its antiviral activity, 97% at 7.5 μM. S4 and S4M4K showed an antiviral activity in vitro when provided 1 h after infection. In vivo experiments in mice by intramuscular injection of non-toxic doses of dermaseptin S4M4K 1 h post-infection by a lethal dose of RABV at the same site allowed more than 50% improvement in mice survival. This study highlights the potential interest of dermaseptins as non-expansive alternatives to rabies immunoglobulins for the treatment of rabies that continues to claim about 60, 000 human lives per year worldwide, almost exclusively in developing countries.